РНК-ферменты - Кавсан, В.М. (Биополимеры и клетка, 1988)
РНК, обладающие каталитическими свойствами благодаря своей способности к специфическому активированию других веществ, названы рибозимами. Обзор посвящен современному состоянию вопроса о каталитической функции РНК. РНК, що володіють каталітичними властивостями завдяки своїй здатності до специфічної активації інших речовин, названо рибозимами. Огляд присвячено сучасному стану питання щодо каталітичної функції РНК. RNA molecules which have catalytic properties are called ribozymes. They were first discovered when studying splicing of Tetrahymena large rRNA, and later it appeared that fungal rRNAs and mitochondrial mRNAs as well as T4 phage mRNA are spliced in the same manner. The present-day data permit suggesting that similar processes may be basic for splicing of all pre-mRNAs bearing introns excluding, probably, some pre-tRNAs. As it has been shown both steps in splicing occur by transeterification, an exchange of phosphate esters, that produces no net change in the number of ester linkages. The ability of RNA molecules to serve as a catalyst of other reactions, including maturation of 5'-end in tRNAs, viroid formation, has emerged. The possible role of ribonucleic acids in catalysis of RNA-polymerization and of biosynthesis of polypeptides in ribosomes is discussed. The review depicts modern state of studies aimed at evaluating the catalytic functions of RNAs.